Attributive N+N compounds in diachrony: the N-modello, N-base and N-limite families - Jan Radimský (Études romanes de Brno)
This article investigates the origin and diachronic development of Attributive-Appositive Noun+Noun (N+N) compounds in Italian, focusing on three semi-schematic families: N-modello, N-base, and N-limite. Drawing on diachronic data from the Google Books corpus, the study examines these compounds' emergence and subsequent productivity evolution from the late 19th century to the present day. The findings highlight the key innovations (leader words) that marked the formation of these patterns and identify significant trends and turning points in the proliferation of these three families of compounds, which have played a crucial role in shaping the broader Attributive-Appositive (ATAP) pattern in Italian. The study is framed within Construction Morphology and Relational Morphology theories, offering insights into the interaction between lexical specificity and abstract constructional patterns.